Terapi Air Putih untuk Dismenorea Primer - Rasyid, Puspita Sukmawaty; Sujawati, Sri; Biki, Yulan (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2021)
Primary dysmenorrhea is a condition of lower abdominal pain that occurs before or during menstruation without any abnormalities or pelvic disease, where the prevalence is higher in the adolescent group, which is 74.42%. The pain experienced has an impact on the disruption of learning activities and concentration. Drinking water is the only means of transporting waste cells that have died from all parts of the body.This study aims to determine the effect of water therapy on primary dysmenorrhea. This type of research is pre-experimental design. The study population was 181 people and a sample of 30 people with accidental sampling technique and met the inclusion criteria. The study was conducted for 1 month. Data were analyzed using paired sample t test. The results of the study: before water therapy most of the young women experienced moderate pain (76.7%) and after therapy, most of them experienced mild pain (73.4%). The results of the paired sample t test value = 0.000. Conclusion; There is an effect of water therapy on primary dysmenorrhea in adolescent girls. Suggestion: The importance of drinking water before and during menstruation to reduce the incidence of dysmenorrhea.